Implementation of rules regarding quarry rehabilitation in Selangor, Malaysia - Yahya @ Yahaya, Zaharah (2018)
Selangor is blessed with an abundant reserve of granite rocks which supplies raw material to develop physical infrastructures in Selangor and the Klang Valley. However, quarry activities affect the environment’s ecosystem and biodiversity resulting in soil erosion, water pollution and visual effects. Quarry rehabilitation can balance between socio-economic, infrastructural development and environmental needs. Generally, the objective of this research is to identify factors hindering quarry rehabilitation in Selangor by examining the existing legislative framework provisions on quarry rehabilitation, investigate the present status of quarry rehabilitation implementation and identify challenges to implement quarry rehabilitation in Selangor. It is a qualitative case study focusing on quarry rehabilitation in Selangor. A document analysis is used to analyze primary legal documents related to quarry rehabilitation, site observation to quarries left without rehabilitation was done to identify the physical appearance of each and focus group discussions with stakeholders were also conducted to attain their inputs. The document analysis of laws and policies related to quarry rehabilitation shows that there are loopholes and ambiguity in the laws and policies, lack of enforcement due to the existing provisions and non-legally binding policies which are not effective. Site observation to quarries left without rehabilitation shows characteristics of environmental degradation with unrestored and unmaintained vegetation and water channels, falling rocks, soil erosions and surface runoffs that results the site to be unstable and hazardous. The focus group discussions with the stakeholders identified 17 factors that challenged the implementation of quarry rehabilitation including operational challenges and enforcement issues. This research shows a pressing need to amend our current legislation to implement quarry rehabilitation in Selangor.